Ecological and health risks assessment of potentially toxic elements in edible plants across mining and non-mining areas of Northwest, Pakistan - Irfan Ullah; Muhammad Adnan; Javed Nawab; Sardar Khan; Muhammad Ishtiaq Jan; Abdullah Jalal; Sajid Ullah (Scientific Reports)
Abstract The current study evaluated the concentrations, ecological and health risks, and phytoremediation potential of potentially toxic elements (PTEs) in soil and edible plant samples from mining and non-mining areas of District Mohmand, Pakistan. Soil and plant samples were collected, oven-dried, acid-digested (HNO3:HCl, 3:1) and analyzed using atomic absorption spectrophotometry (Perkin-Elmer AA400). Traditionally, many of the studied plant species serve both as food and in ethnomedicines. Results indicated elevated mean concentrations of Cr, Cu, Mn, Ni, Pb, Fe, and Zn in both soil and edible plant samples from mining area compared to non-mining area. In plant tissues, PTE concentrations frequently exceeded permissible limits, particularly in samples from mining areas. Ecological risk assessments classified the mining areas as moderately to severely contaminated. Health risk indices further indicated potential carcinogenic and non-carcinogenic effects from consuming plants grown in polluted site. In contrast, samples from non-mining site posed minimal ecological and health risks. Some plant species exhibited bioaccumulation factors (BAF) > 1, suggesting their potential use in phytoremediation. Overall, the findings suggest the urgent need for monitoring and managing PTEs contamination in mining region to mitigate associated environmental and public health risks.